2021
DOI: 10.1007/s00221-021-06158-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparative experimental study of visual brain event-related potentials to a working memory task: virtual reality head-mounted display versus a desktop computer screen

Abstract: Virtual reality head mounted display (VR HMD) systems are increasingly utilised in combination with electroencephalography (EEG) in the experimental study of cognitive tasks. The aim of our investigation was to determine the similarities/differences between VR HMD and the computer screen (CS) in response to an n-back working memory task by comparing visual electrophysiological event-related potential (ERP) waveforms (N1/P1/P3 components). The same protocol was undertaken for VR HMD and CS with participants wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…This situation may have negatively affected the design process in VR. Previous studies have shown that the weight and bulk of VR headsets can cause some level of discomfort among participants (Aksoy et al, 2021;Rupp et al, 2019), which is also consistent with questionnaire comments from two participants. Some level of frustration caused by the stress and the weight of the VR headsets may have prevented the participants from focusing on the design, resulting in longer design duration and slower design speed in virtuo.…”
Section: Eem Design Actions and Durationssupporting
confidence: 87%
“…This situation may have negatively affected the design process in VR. Previous studies have shown that the weight and bulk of VR headsets can cause some level of discomfort among participants (Aksoy et al, 2021;Rupp et al, 2019), which is also consistent with questionnaire comments from two participants. Some level of frustration caused by the stress and the weight of the VR headsets may have prevented the participants from focusing on the design, resulting in longer design duration and slower design speed in virtuo.…”
Section: Eem Design Actions and Durationssupporting
confidence: 87%
“…Our feature extraction method relies on a general tendency that only appears by averaging large amounts of data belonging, ideally, to the largest possible number of subjects (and or tasks according to the case) to train the data. The literature of EEG has previously presented cases in which features are only observable after using grand averages of data, such as in the case of event related potentials (Hoehl and Wahl, 2012 ; Voigt-Antons et al, 2012 ; Kuncheva and Rodríguez, 2013 ), also including specific cognitive tasks such as n-back (Aksoy et al, 2021 ) and the readiness potential (“Bereitschaftspotential”) (Blankertz et al, 2007 ; Nann et al, 2019 ), where grand averages have a noise canceling effect in the signals, and some of these event related potentials, occurring at longer latencies after stimuli are more related to endogenous brain states (Nunez, 2012 ; Sellers et al, 2012 ), like the ones we are looking for. We have presented a simple classification method with channel selection based on a general tendency in the data obtained along the whole durations of trials which should relate mental workload to a more permanent or endogenous characteristic of mental activity.…”
Section: Methodsmentioning
confidence: 99%
“…cognitive tasks such as n-back (Aksoy et al, 2021) and the readiness potential ("Bereitschaftspotential") (Blankertz et al, 2007;Nann et al, 2019), where grand averages have a noise canceling effect in the signals, and some of these event related potentials, occurring at longer latencies after stimuli are more related to endogenous brain states (Nunez, 2012;Sellers et al, 2012), like the ones we are FIGURE Illustration of the "Theta Negative" Matrix TN ( × ), and vector mean_tr ( × ) corresponding to the total trials of task T . Collected from all the twelve subjects considered for analysis from our dataset (each subject performed trials of task T ), each trial (previously preprocessed, filtered through the theta frequency band, trimmed and scaled) is represented by a vector ( × ), obtained after finding an average per EEG channel of all the sample components that had a negative amplitude in that channel.…”
Section: Figurementioning
confidence: 99%
“…Additionally, a study explored a cognitively adaptive VR training system incorporating realtime EEG to adjust task difficulty, revealing significant brain activity changes with increasing complexity while response times remained unchanged (Dey et al, 2019). Furthermore, a study explored the integration of VR headsets with EEG in cognitive tasks, confirming that VR head-mounted displays (HMDs) could successfully elicit ERP components similar to traditional computer screens, indicating their potential utility in early ERP investigations for cognitive research (Aksoy et al, 2021). These studies collectively demonstrate the evolving landscape of WMT, underscored by the promising prospects of BCI-VR, offering more immersive and quantifiable approaches to cognitive enhancement.…”
Section: Bci-vr In Wm Training and Evaluationmentioning
confidence: 99%